2018
DOI: 10.1016/j.cell.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Short Tandem Repeats Co-localize with Chromatin Domain Boundaries

Abstract: More than 25 inherited human disorders are caused by the unstable expansion of repetitive DNA sequences termed short tandem repeats (STRs). A fundamental unresolved question is why some STRs are susceptible to pathologic expansion, whereas thousands of repeat tracts across the human genome are relatively stable. Here, we discover that nearly all disease-associated STRs (daSTRs) are located at boundaries demarcating 3D chromatin domains. We identify a subset of boundaries with markedly higher CpG island density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 65 publications
(100 reference statements)
7
141
2
1
Order By: Relevance
“…For example, a 20bp eSTR was associated with nine eGenes (seven lead) connected via distal loops ( Figure 6E) and was in strong LD with a UKBB variant linked to 19 distinct traits including asthma and body fat percentage; two of the genes associated with this variant (TCF20 and POLR3H) have also been previously linked to autism (Babbs et al, 2014;Kong et al, 2012). We observed that this variant appears to overlap a chromatin subdomain boundary visible in Hi-C data from iPSCORE which is notable given that disease causing STRs, such as the causal variant for Fragile X syndrome, have been reported to localize to subdomain boundaries (Sun et al, 2018). Additionally, we found a 13kb deletion on chromosome 7 linked to five eGenes via looping that was also linked to 14 traits ( Figure 6F).…”
Section: Ld Tagging and Gwas Associations Differ Between Variant Classessupporting
confidence: 49%
“…For example, a 20bp eSTR was associated with nine eGenes (seven lead) connected via distal loops ( Figure 6E) and was in strong LD with a UKBB variant linked to 19 distinct traits including asthma and body fat percentage; two of the genes associated with this variant (TCF20 and POLR3H) have also been previously linked to autism (Babbs et al, 2014;Kong et al, 2012). We observed that this variant appears to overlap a chromatin subdomain boundary visible in Hi-C data from iPSCORE which is notable given that disease causing STRs, such as the causal variant for Fragile X syndrome, have been reported to localize to subdomain boundaries (Sun et al, 2018). Additionally, we found a 13kb deletion on chromosome 7 linked to five eGenes via looping that was also linked to 14 traits ( Figure 6F).…”
Section: Ld Tagging and Gwas Associations Differ Between Variant Classessupporting
confidence: 49%
“…This is complemented by evidence for insulator function of specific TE families (Wang et al 2015;Schmidt et al 2012). More recently, an association between the expansion of disease-associated tandem repeats and three-dimensional chromatin topology has been reported, highlighting the role of these elements for healthy cellular function (Sun et al 2018). However, despite their functional relevance, the establishment of a causal relationship between TE genomic location and three-dimensional chromatin organisation has been hindered by the lack of observations in a dynamic system that would allow the examination of changes in chromatin conformation related to TEs.…”
Section: Introductionmentioning
confidence: 87%
“…lead to partial ATM activation [48]. A recent study has shown that repeat expansion disease genes, including HTT, localize to boundaries of chromatin domains associated with defined chromatin topology [57]. The study provided evidence in Fragile X syndrome, a disease caused by CGG expansions in the FMR1 gene, that pathological repeat expansions are associated with disrupted chromatin boundaries and, by extension, genomic topography [57].…”
Section: Increased Asymmetric Divisionmentioning
confidence: 97%
“…A recent study has shown that repeat expansion disease genes, including HTT, localize to boundaries of chromatin domains associated with defined chromatin topology [57]. The study provided evidence in Fragile X syndrome, a disease caused by CGG expansions in the FMR1 gene, that pathological repeat expansions are associated with disrupted chromatin boundaries and, by extension, genomic topography [57]. Thus, it is conceivable that the HTT CAG repeat expansion in HD also leads to altered chromatin structure, triggering partial ATM activation and elevated genome integrity signaling.…”
Section: Increased Asymmetric Divisionmentioning
confidence: 99%